2011
DOI: 10.7326/0003-4819-155-3-201108020-00004
|View full text |Cite
|
Sign up to set email alerts
|

Primary and Secondary Syphilis Among Black and Hispanic Men Who Have Sex With Men: Case Report Data From 27 States

Abstract: Centers for Disease Control and Prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
50
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 35 publications
3
50
0
1
Order By: Relevance
“…1 Similarly, from 2005 to 2008, rates of reported P&S syphilis increased 74% among black MSM (adjusted for age and region of U.S.), and 160% and 117% among 15-19 and 20-24 year olds, respectively (adjusted for age, region, and race/ethnicity). 2 Furthermore, analysis of trends in HIV and P&S syphilis from 2004 to 2008 found that increases among black men 13-24 years old were identified in nearly all parts of the U.S. included in the study indicating that the increases were widespread rather than limited to a few areas. 3 For both diseases, it is possible that increases among MSM began earlier.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Similarly, from 2005 to 2008, rates of reported P&S syphilis increased 74% among black MSM (adjusted for age and region of U.S.), and 160% and 117% among 15-19 and 20-24 year olds, respectively (adjusted for age, region, and race/ethnicity). 2 Furthermore, analysis of trends in HIV and P&S syphilis from 2004 to 2008 found that increases among black men 13-24 years old were identified in nearly all parts of the U.S. included in the study indicating that the increases were widespread rather than limited to a few areas. 3 For both diseases, it is possible that increases among MSM began earlier.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 From 2006 to 2009, estimated HIV incidence increased 35% among MSM 13-29 years old and 48% among black MSM 13-29 years old. 1 Similarly, from 2005 to 2008, rates of reported P&S syphilis increased 74% among black MSM (adjusted for age and region of U.S.), and 160% and 117% among 15-19 and 20-24 year olds, respectively (adjusted for age, region, and race/ethnicity).…”
Section: Introductionmentioning
confidence: 99%
“…With regard to HIV risk, Black YGBMSM accounted for more than half of new HIV infections among YGBMSM in 2010, and rates of HIV infection continue to be disproportionately represented among this population (Centers for Disease Control, 2011Control, , 2013Hall et al, 2007;Harawa et al, 2004). Sexually transmitted infections (STIs)-including syphilis, gonorrhea, and chlamydia-are noted to be higher among Black GBMSM, which may in turn predispose this population to greater risk for HIV infection (Millett et al, 2006;Newman & Berman, 2008;Su, Beltrami, Zaidi, & Weinstock, 2011). Moreover, HIVpositive Black GBMSM are less likely to receive treatment or see a health care provider shortly after being diagnosed, and are also less likely to have health insurance than other HIV-positive GBMSM (Ebrahim, 2004;Millett et al, 2012;Oster, Dorell, et al, 2011;Oster, Wiegand, et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…населения. Повысилась также заболевае-мость сифилисом скрытым ранним (на 12,4%) и скрытым поздним (на 9,9%), причем 43,2% заболев-ших составили афроамериканцы [4][5][6][7]. На протя-жении 2006-2011 гг.…”
unclassified